Study guides

Q: A plus 3b plus 5a plus 4b?

Write your answer...

Submit

Related questions

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

No

20a2b2

6a+7b. This cannot be simplified anymore unless you know a or b.

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b

1a+3b 2a+4b=3a +7b

9a + 3b - 11a - 4b = -2a -b

2a + 4b

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b

6+7a+6b

-6(a-3b-9c)

8a+b+32a+3b=40a+4b

equals 3b

4b

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

It is not an equation but an algebraic expression that can be simplified to: 12b-5a

It is: 4b+6

11a+11b

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

-2a plus 3b

12a + 6b + 6c = 6(2a + b + c)

9a + 7b *remember to look and understand the letters!*

2a + 3b